Pengaruh Penyuluhan Media Puzzle Tentang Konsumsi Sayur Dan Buah Terhadap Peningkatan Pengetahuan Sikap Dan Tindakan Siswa Di SD Negeri Arul Cincin Kecamatan Pintu Rime Gayo Kabupaten Bener Meriah Provinsi Aceh - Inike Ipak Kuine; Athira Demitri (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Not consuming enough fruit and vegetables can result in the body experiencing a lack of nutrients such as vitamins, minerals and fiber, which can lead to various diseases. Objective The aim of the research is to determine the success of the influence of puzzle media education on vegetable and fruit consumption on increasing students' knowledge and actions at SDN Alur Cincicn, Pintu Rime Gayo District, Bener Meriah Regency, Aceh Province. Method uses a quasi-experiment with a one group pre-test approach, a design test, namely measurements carried out before and after the intervention to see the results of changes. The score obtained from the attitude pre-test was 3.77 and the average post-test score was 7.87. The score obtained from the pre-test action regarding vegetable and fruit consumption was 6.67 and the average post-test score was 9.00. It is hoped that the school will collaborate with the Health Service and the nearest Community Health Center to pay more attention to the importance of nutrition education in schools to help increase students' knowledge about the importance of consuming fruit and vegetables as part of efforts to improve the quality of students at regional and national levels.